The Labour Injunction in Canada - Carrothers, Alfred (Relations industrielles / Industrial Relations, 1958)
SummaryThis is an outline of the law of the injunction as used in labour disputes in the common-law provinces, with particular reference to recent developments in the law of picketing. The Author has prepared this essay for an audience not trained in law.